Strategies used by nurses to minimize the occurrence of delirium in critically ill patients - Oliveira, Katherine Pithon (2020)
Objective: to describe the strategies used by nurses to minimize the occurrence of delirium in patients admitted to the intensive care unit (ICU). Method: exploratory-descriptive study, with a qualitative approach, developed in a large public teaching hospital in the city of Salvador. It was carried out in September and October 2018, 16 nurses participated in the study. Data were collected through semi-structured interviews and analyzed using the “Thematic Content Analysis Technique”. Results: from the data analysis, two thematic categories emerged, named: “Lack of knowledge about monitoring delirium in the ICU” and “Strategies of nurses to minimize the occurrence of delirium in the ICU”. Conclusion: although the nurses' lack of knowledge about delirium, there is a coherence in the methods of interventions to prevent it. The implementation of protocols and educational activities are essential to empower nurses regarding the interventions performed.